Highland devil - Howell, Hannah (Howell, Hannah. Murrays., 2018)
When a red-haired woman tries to steal Sir Gybbon Murray<U+2019>s horse on his journey back to the Murray stronghold, he thanks his lucky stars that his horse is a rude lout<U+2014>and that the pretty thief is not so injured that she can<U+2019>t tell her tale. He<U+2019>s no nursemaid to delicate lasses, but Mora Ogilvy is fleeing her ruthless cousins, fearing for her life. And when she tells him of the home they<U+2019>ve taken from her and the man they say she murdered, Gybbon cannot let such injustice stand . . . Mora<U+2019>s pride demands she take back her lands, but not by risking the lives of this handsome, wicked knight and his family. Still, she needs to recover from her wounds, and staying close to Gybbon in his brother<U+2019>s keep is a seductive solution. A few weeks at his side will be a sweet memory for her when she returns to fight her own battles. Except the depth of her cousins<U+2019> treachery<U+2014>and the fierceness of Gybbon<U+2019>s love<U+2014>may turn her own heart against her plans . . .